Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4314/sajas.v44i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Nigella seed oil as alternative to avilamycin antibiotic in broiler chicken diets

Abstract: This study was conducted to study the effect of nigella seed oil as an alternative to the antibiotic, avilamycin, on growth, digestibility, muscle fatty acid profile and some physiological parameters in broiler chickens. Fifty four chicks at 15 d of age (average weight, 320 ± 3 g) were divided into a control group and two treatment groups (n = 18). The control group was fed a basal diet and the experimental treatment groups were fed the basal diet supplemented with avilamycin at a level of 0.001% or nigella se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
29
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 29 publications
(21 reference statements)
10
29
1
Order By: Relevance
“…Furthermore, no increase in serum concentration of ALT and AST may provide evidence to protect of liver against hepatocellular degeneration (Al-Jaff, 2011). The presented study confirmed previous results (Habibi, et al, 2014;Saleh, 2014;Zhu, et al, 2014) on the decreasing effect of phytoadditives on the activities of plasma ALT and AST in animals. Meanwhile, Abd ElGhang and Ismail (2013) who used oregano essential oil in broiler feed, observed increase in the activity of ALT and AST.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, no increase in serum concentration of ALT and AST may provide evidence to protect of liver against hepatocellular degeneration (Al-Jaff, 2011). The presented study confirmed previous results (Habibi, et al, 2014;Saleh, 2014;Zhu, et al, 2014) on the decreasing effect of phytoadditives on the activities of plasma ALT and AST in animals. Meanwhile, Abd ElGhang and Ismail (2013) who used oregano essential oil in broiler feed, observed increase in the activity of ALT and AST.…”
Section: Resultssupporting
confidence: 81%
“…In our study, significantly higher (P <0.01) concentration of ALT as well as AST was found in turkey of control group (53.963 and 6.238 U/l), while lower concentration was found in birds from experimental group (3.499 and 1.012 U/l). The lowest activities for Gálik et al: Effect Of A Phytogenic Additive On Blood Serum Indicator Levels And Fatty Aci... plasma ALT and AST recorded for individuals fed diets supplemented with phytoadditive indicate that the used treatment did not negatively alter liver enzyme activity but also had a non-toxic effect on the kidneys and liver (Saleh, 2014). Furthermore, no increase in serum concentration of ALT and AST may provide evidence to protect of liver against hepatocellular degeneration (Al-Jaff, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, no increase in serum concentration of ALT and AST may provide evidence to protect of liver against hepatocellular degeneration (Al-Jaff, 2011). Presented experiment did not confirm results of other authors (Habibi et al, 2014;Saleh, 2014;Zhu et al, 2014). Shi et al (2014) who added phytosterols into feed mixture of layers reported some minor changes in clinical chemistry parameters, but these changes were small and considered to be of no toxicological significance.…”
Section: Blood Parameters Of Laying Henscontrasting
confidence: 50%
“…In contrast to the present study, significantly higher concentrations of ALT as well as AST were found in the control group, while lower concentration was detected in birds from experimental group. The lowest activities for plasma ALT and AST recorded for individuals fed diets supplemented with phytoadditive indicate that the used treatment did not negatively alter liver enzyme activity but also had a non-toxic effect on the kidney and liver (Saleh, 2014). Furthermore, no increase in serum concentration of ALT and AST may provide evidence to protect of liver against hepatocellular degeneration (Al-Jaff, 2011).…”
Section: Blood Parameters Of Laying Hensmentioning
confidence: 99%
“…This result is in agreement with the results of Ceylan and Ciftci (2003), Chowdhury et al (2009) and Eseceli et al (2010), who reported that there was no significant effect on carcass weight in broiler chicks fed a diet supplemented with avilamycin. Similarly, Saleh (2014) reported that supplementation with avilamycin did not significantly affect the liver weight of broilers.…”
Section: Carcass Traitsmentioning
confidence: 99%